1996
DOI: 10.1039/an9962100687
|View full text |Cite
|
Sign up to set email alerts
|

Study of the effect of lanthanide ions on the kinetics of glutamate dehydrogenase by a chronoamperometric method

Abstract: A chronoamperometric method, based on the oxidation of reduced nicotinamide adenine dinucleotide (NADH) on a glassy carbon electrode, for assaying glutamate dehydrogenase activity is described. Once the reaction was initiated by addition of enzyme into a well stirred assay mixture containing NADH, the concentration of NADH and the steady-state limiting current of NADH oxidation on the electrode decreased linearly in a short time range from the start of the reaction. The rate of the enzyme-catalysed reaction ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…With the increase of Al(III) concentrations (30- 80 lM), the enzyme GDH activity was activated. It was known that the step of dissociation of the NAD + ÀGDH complex is the rate-limiting step in the reductive amination reaction [35]. However, our voltammetry studies indicated that Al(III) could interrupt the binding of NAD + to GDH when the concentration of metal ion is increased.…”
Section: Biological Effectsmentioning
confidence: 78%
See 1 more Smart Citation
“…With the increase of Al(III) concentrations (30- 80 lM), the enzyme GDH activity was activated. It was known that the step of dissociation of the NAD + ÀGDH complex is the rate-limiting step in the reductive amination reaction [35]. However, our voltammetry studies indicated that Al(III) could interrupt the binding of NAD + to GDH when the concentration of metal ion is increased.…”
Section: Biological Effectsmentioning
confidence: 78%
“…Electrochemical analysis has been recognized as a powerful tool for measuring trace metal ions and biomolecules in the biological system [35]. Its remarkable sensitivity, simple instrumentation, low cost, simple operation procedure, fast and reliable results and many other advantages make it satisfactory for many biological system analyses [36,37].…”
Section: Biological Effectsmentioning
confidence: 99%
“…One of the few convective electrode systems is the rotating disk electrode. Based on the diffusion layer approach described by Bard and Faulkenr,[19] Xin and Gao [16] developed a chronoamperometric method using a disk electrode in a well-stirred solution. It is assumed that convection maintains a uniform concentration of all species that are equal to the bulk values up to a certain distance, i.e., the "diffusion" layer thickness (d) at the electrode fed by convective transfer.…”
Section: Theoretical Considerationmentioning
confidence: 99%
“…In addition, NADH may be monitored by oxidation at an electrode surface and this oxidation reaction has well been studied [13 -15]. In 1996, Xin and Gao proposed a chronoamperometric method to evaluate the initial kinetics of the enzyme-catalyzed reaction [16] and their method represents a significant advance. One of the advantages of the method is that it could be used to obtain the real initial reaction rate.…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical analysis has always been recognized as a powerful tool for measuring trace metal ions and biomolecules in the biological system. Its remarkable sensitivity, simple instrumentation, lower costs, simple operation procedure, faster and reliable results and many other advantages make it satisfy many requires and extensively applied in different biological system analysis or in other fields [16]. In the past, we have investigated the interactions of Al (III) with the substrates (α-KG/ L-Glu) [17,18] and coenzyme I (NAD + /NADH) [19,20] of the GDH enzyme system.…”
Section: Introductionmentioning
confidence: 99%